Political aestheticization in the representation of Balinese selonding gamelan: between cultural practices and identity strategies - Setiyono, Budi (International Journal of Visual and Performing Arts, 2025)
Selonding Gamelan in Tenganan Pegringsingan Village, Bali, plays an important role in the traditional MekarÃ©-kare ritual and represents the close relationship between art and the social structure of the local community. This study aims to reveal how the aesthetics of Selonding Gamelan are mobilized as a symbolic strategy in responding to external influences on the local cultural order. Using ethnographic and participatory observation methods, especially in the context of the MekarÃ©-kare ritual, this study finds that Selonding Gamelan not only functions as a musical instrument, but also as a cultural medium that dampens elements of violence, negotiates identity, and strengthens social cohesion. Gamelan aesthetics are used consciously as a mechanism for protecting customary values against external cultural intervention. The conclusion of this study shows that ritual art has a transformative power in shaping the collective identity and cultural sovereignty of traditional communities. These findings open up new space for studying the relationship between art, ritual, and politics in the study of Nusantara performing arts.